Effect of Adrenomedullin on Adrenergic Vasoconstriction in Mesenteric Resistance Arteries of the Rat - Shinji Akiyama; Yukako Hatanaka; Narumi Hobara; Jin Honghua; Keiji Kosugi; Fusako Takayama; Hiromu Kawasaki (Elsevier, 2005)
Adrenomedullin (AM) is a hypotensive peptide that belongs to a family of peptides structurally related to calcitonin gene-related peptide (CGRP). The present study examined the effect of AM on adrenergic nerve-mediated vasoconstriction in rat perfused mesenteric vascular beds without endothelium. Perfusion of AM at 0.1 nM but not 10 nM increased vasoconstrictor responses to periarterial nerve stimulation (PNS) (1 - 4 Hz), while AM at 10 nM significantly attenuated vasoconstriction induced by bolus injection of norepinephrine (NE). In preparations treated with capsaicin (a CGRP depletor), pressor responses to both PNS and NE injection were markedly attenuated by AM. Perfusion of CGRP(8 - 37) (a CGRP-receptor antagonist) significantly potentiated the PNS- but not the NE-induced vasoconstriction. Combined perfusion of CGRP(8 - 37) and AM had no effect on the PNS-induced response and antagonized the inhibitory effect of AM on the NE-induced response. AM(22 - 52) (an AM-receptor antagonist) did not influence the effect of AM. These findings suggest that AM facilitates adrenergic vasoconstriction by inhibiting neurotransmission of CGRP-containing nerves, which counteract adrenergic nerve-mediated vasoconstriction. Keywords:: adrenomedullin, adrenergic vasoconstriction, calcitonin gene-related peptide (CGRP), neurotransmission of CGRP-containing nerves, rat mesenteric resistance artery